A Community Based Research: Building Healthy Living Community through Sports and Nutrition Program - Syamsuar Abbas; Reflianto (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2018)
Purpose of this research was to analysis the effect of the community-based research program for building the healthy living community through sports and nutrition programs in Padang Pariaman regency. Targets of this program were to build a sports community and nutrition in Nagari Pauh Kamba, to synergize the role of sport community to be more aware of the importance of nutrition for the health and to encourage the community systems to strengthening the exercises and people nutrition program. Method of this research was a community-based research. It was a project carried out during the three months in building a sports community and nutrition in Rimbo Dulang-Dulang, Bayur and Pinang villages, Nagari Pauh Kamba. Results of this research reported that the program can be done well and enable to increase public awareness for the health and nutrition. The comparison of people awareness before and after doing the program revealed some positive effects on people health and nutrition